Energy Loss of Magnetic Coupling for Pump - Jiaqiong Wang; Jundong Duan; Ruijie Zhang; Jingru Sun (Energies)
To investigate the energy loss characteristics of magnetic pumps, an experimental setup for magnetic transmission in pumps was constructed. Through experiments, the impact of various factors on the eddy current loss of the magnetic coupling was examined, including rotational speed, electrical conductivity of the isolation sleeve material, axial coupling length of the magnetic coupling, and the physical properties of the fluid medium. Additionally, the temperature variation at different axial positions along the isolation sleeve was measured. The results indicated that eddy current loss increases with higher rotational speeds and shows a nearly linear relationship with the axial coupling length of the magnetic coupling. Furthermore, as the conductivity of the isolation sleeve material rises, the eddy current loss also increases linearly. The conductivity and viscosity of the fluid medium were found to have negligible effects on eddy current loss. Friction losses due to the liquid medium inside the metal isolation sleeve were much smaller than the eddy current losses generated by the sleeve, and thus can be ignored. For non-metallic isolation sleeves, the energy loss is primarily attributed to fluid friction. Finally, the temperature along the axial direction of the isolation sleeve increases progressively from the flange to the bottom.